Integrating agroecology into public policies in Senegal - Milhorance, Carolina; Camara, Astou; Sourisseau, Jean-Michel; Piraux, Marc; Mane, Chérif Assembène; Sirdey, Ninon; Belmin, Raphaël; Ka, Dié-Yacine; Sall, Moussa; Sall, Mame Cheikh Anta (2024)
This report analyses the emergence of agroecology on the political agenda, it examines agricultural policies and their obstacles to agroecology, describes challenges and prospects for the institutionalization of agroecology, analyzing the stakeholder strategies in this process and the institutional and structural constraints to the deployment of agroecology policies and final considerations draws lessons and prospects on this theme.